New adaptively secure key-policy attribute-based encryption scheme - Song LUO; Zhong CHEN (Tongxin xuebao)
A new key-policy attribute-based encryption scheme based on 3 dimension dual orthonormal bases was proposed.This scheme was constructed in prime order groups with adaptive security and supporting access structures.It has been proved the security from decisional linear assumption by using dual system encryption technique.Compared with previous key-policy ABE scheme which is also adaptively secure,the scheme is more efficient at the same security level.